IMPLEMENTATION OF PATIENT SAFETY UNDER MINISTRY OF HEALTH HOSPITAL ACCREDITATION STANDARDS - Hermawan, Afan; Dinda Iryawati (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2022)
Patient safety is a serious global concern in health services. The implementation of patient safety in hospitals refers to the Patient Safety Goals (SKP), according to the Decree of the Minister of Health of the Republic of Indonesia Number HK.01.07/Menkes/1128/2022. The purpose of this study was to evaluate the implementation of SKP in Maternal and Child Hospitals according to the 2022 Ministry of Health accreditation standards. The study used qualitative methods through interviews, documentation, and observations. Informants in this study were management and staff. From the results obtained from a policy perspective, the implementation of SKP 2, 4, 5, and 6 at RSIA Nuraida is complete. This condition was found to be different from the results of documentation and observation, where SKP 1, 3, 4, and 6 had reached the Ministry of Health standard, which was 100%. For SKP 2 the achievement of 80% is because the officers have not mastered communication methods well, so the recording is incomplete. While the cause of the achievement of SKP 5 only reached 84% because the officers did not carry out hand washing according to the SPO. The SKP implementation at RSIA Nuraida concludes that it almost meets the 2020 Ministry of Health accreditation standards. This can be seen from 4 of the 6 SKP fields that have reached the 100% standard. Suggestions that might be recommended are hospital management to develop policy directions related to SKP along with socialization, placing human resources who have the expertise, ability, and willingness in the field of accreditation, ensuring that SKP is implemented by each unit through the PMKP Committee by having periodic simulation programs and filling in data. ISKP every month, making experience sharing activities, and briefings on patient safety issues.